Health-related outcomes of youth sport participation: a systematic review and meta-analysis - Dennis Bengtsson; Joar Svensson; Virginia Wiman; Andreas Stenling; Erik Lundkvist; Andreas Ivarsson (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Participating in youth sports can benefit individuals’ psychological (e.g., fewer depressive symptoms, improved self-esteem), social (e.g., improved social skills, learning to work with others as a team), and physical health-related outcomes (e.g., higher physical activity levels, lower body fat), aligning with global sustainable development goals. Nevertheless, little is known about the magnitude concerning the effects of youth sport participation on such health-related outcomes compared with nonparticipation over time from childhood to adulthood. In this paper, we systematically review the extant longitudinal research and estimate the effects of youth sport participation on several psychological, physical, and social outcomes compared with nonparticipation. Methods Electronic database searches were employed to identify English-language peer-reviewed studies published from the earliest date until October 4, 2024. By using a priori criteria for inclusion and exclusion, we included 46 out of 4588 identified individual studies in the systematic review and 38 of the eligible studies for calculation of Cohen’s d effect size estimates. Results Together, the follow-up measurements of the included studies varied from 1 to 54 years after baseline, and the sample sizes ranged from 76 to over 50,000 participants. The meta-analysis revealed that youth sport participation had positive and statistically significant low- to medium-sized effects on physical activity, health and wellbeing, and negative small- to medium-sized effects on unhealthy body composition and mental ill-being over time. Conclusions This study provides evidence that participating in youth sports can have health-promoting effects throughout childhood, adolescence, and adulthood. This advocates for collaborative efforts among national governments, sport governing bodies, communities, and sports clubs to create an accessible and inclusive youth sport environment where young people can thrive and reap the health benefits of sport participation.